Primary cilia‐regulated transcriptome in the renal collecting duct. Issue 7 (8th February 2018) - Mohammed, Sami G.; Arjona, Francisco J.; Verschuren, Eric H. J.; Bakey, Zeineb; Alkema, Wynand; van Hijum, Sacha; Schmidts, Miriam; Bindels, Rene J. M.; Hoenderop, Joost G. J.
Abstract : Renal tubular cells respond to mechanical stimuli generated by urinary flow to regulate the activity and transcript abundance of important genes for ion handling, cellular homeostasis, and proper renal development. The primary cilium, a mechanosensory organelle, is postulated to regulate this mRNA response. The aim of this study is to reveal the transcriptome changes of tubular epithelia in response to fluid flow and determine the role of primary cilia in this process. Inner‐medullary collecting duct (CD) cells were subjected to either static or physiologically relevant fluid flow (~0.6 dyn/cm 2 ). RNA‐sequencing analysis of ciliated cells subjected to fluid flow showed up‐regulation of 1379 genes and down‐regulation of 1294 genes compared with static control cells. Strikingly, only 54 of these genes were identified as gene candidates sensitive to primary cilia sensing of fluid flow, of which 16 were linked to ion or water transport pathways in the CD. Validation by quantitative real‐time PCR revealed that only the expression of transferrin receptor, which is involved in iron transport; and tribbles pseudokinase 3, which is involved in insulin signaling, were unequivocally regulated by primary cilia sensing of fluid flow. This study shows that the involvement of primary cilia in ion transport in the collecting duct is exceptionally specific.—Mohammed, S.G., Arjona, F.J., Verschuren, E.H.J., Bakey, Z., Alkema, W., van Hijum, S., Schmidts, M., Bindels, R.J.M., Hoenderop, J. G. J. Primary cilia‐regulated transcriptome in the renal collecting duct. FASEB J. 32, 3653–3668 (2018). www.fasebj.org